Family satisfaction in young women - Quezada Zevallos, Jenny (2015)
The concept of family satisfaction is rarely analyzed in its dimensions; the objective of this study is to analyze the dimensions contained in the Family Satisfaction Scale by Adjectives, known by its acronym in Spanish - ESFA. This is a descriptive study; the sample consisted of 85 women between 16 to 24 years old. The instrument to be used is the ESFA.Results: The scale has an adequate content validity, validated through the technique of judging criteria. The global statistical reliability is high (Alpha de Cronbach .917 y un Coeficiente Guttman Split-Half de .934).The ESFA scale items, according to a jury of 4 specialists in the Family area. They grouped the same ones in 2 dimensions each of them conformed by two elements: I. Family Love (Holding and Sense of belonging to the family) and II. Happiness ( Joy and Tranquility). The group of study presents a High level of Family Satisfaction, and in all dimensions and elements a High level.